1995
DOI: 10.1007/s001250050435
|View full text |Cite
|
Sign up to set email alerts
|

Decreased non-esterified fatty acid suppression and features of the insulin resistance syndrome occur in a sub-group of individuals with normal glucose tolerance

Abstract: SummaryTo investigate causes of increased triglyceride concentrations in subjects with normal glucose tolerance (determined by oral glucose tolerance testing using World Health Organization criteria) 883 healthy subjects (389 men and 494 women) between 40 and 65 years of age were studied. Subjects were divided by gender into four groups according to 120-rain glucose concentrations. Individuals in the highest quartile of glucose concentration had the highest mean triglyceride concentrations (p < 0.0001) and hig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
10
0
2

Year Published

1999
1999
2010
2010

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 17 publications
0
10
0
2
Order By: Relevance
“…At baseline and at follow‐up, two measures of NEFA suppression were determined: (i) NEFA area and (ii) ΔNEFA/insulin increment. NEFA area was calculated as a measure of the overall NEFA response during the OGTT and was defined as the area under the trapezoid described by the NEFA measurements at 0, 30 and 120 min[29,30]. The units of this measure are mmol/l/h.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…At baseline and at follow‐up, two measures of NEFA suppression were determined: (i) NEFA area and (ii) ΔNEFA/insulin increment. NEFA area was calculated as a measure of the overall NEFA response during the OGTT and was defined as the area under the trapezoid described by the NEFA measurements at 0, 30 and 120 min[29,30]. The units of this measure are mmol/l/h.…”
Section: Methodsmentioning
confidence: 99%
“…The 120 min time point was excluded from the ΔNEFA/insulin increment variable since measurement of 120 min (or fasting) plasma NEFA concentrations discriminates poorly between subjects with different degrees of insulin resistance[2,29–31]. Thus, the gradient between NEFA concentrations at fasting and 120 min does not provide a good measure of insulin‐mediated NEFA suppression if the 30 min NEFA level is not taken into account.…”
Section: Methodsmentioning
confidence: 99%
“…Ïîêàçàíî, ùî íàâ³òü ïîì³ðíî ï³äâèùåíà êîíöåíòðàö³ÿ ñå÷îâî¿ êèñëîòè (ÑÊ) çóìîâëþº çá³ëüøåííÿ ðèçèêó ã³ïåðòåí糿, ÖÄ 2ãî òèïó, ôàòàëüíèõ ñåðöåâî-ñóäèííèõ ïîä³é. Êð³ì òîãî, âíàñë³äîê ïîãàíî¿ ðîç÷èííîñò³ ÑÊ âèïàäຠó âèãëÿä³ êðèñòàë³â ó ð³çíèõ îðãàíàõ, ïîðóøóþ÷è ì³êðîöèðêóëÿö³þ òà âèêëèêàþ÷è ðåàêòèâíå çàïàëåííÿ â ñóãëîáàõ ³ â íèðêàõ [1,3,12,20]. Ïðîäåìîíñòðîâàíî àñîö³àö³þ ÃÓ ç âèñîêèì ðåíàëüíèì ³ çàãàëüíèì ñóäèííèì îïîðîì, ùî ïîâÿçàíî ç ïîðóøåííÿì åíäîòåë³àëüíî¿ ïðîäóêö³¿ òà á³îäîñòóïíîñò³ NO, à òàêîae ç³ âïëèâîì íà ðåí³í-àíã³îòåíçèíîâó ñèñòåìó [30].…”
unclassified
“…Ïàðàëåëüíî äî çíèaeåííÿ âì³ñòó àíäðîãåí³â ó ÷îëîâ³ê³â çðîñòຠê³ëüê³ñòü àáäîì³íàëüíîãî (â³ñöåðàëüíîãî) aeèðó. ³äîìî, ùî äåô³öèò òåñòîñ ò å ð î í ó ñ è ë ü í è é ñ ò è ì óë ÿ òî ð ð î ñ òó â³ñöåðàëüíèõ àäèïîöèò³â, âèñîêà ìåòàáî-ë³÷íà àêòèâí³ñòü ÿêèõ ñïðèÿº ïîñèëåíîìó ðîçïàäó òðèãë³öåðèä³â ç óòâîðåííÿì â³ëüíèõ aeèðíèõ êèñëîò, ÿê³ âèêëèêàþòü ³íñóë³íî-ðåçèñòåíòí³ñòü ãåïàòîöèò³â [2,3,12,16].Ó â³äïîâ³äü íà öå ðîçâèâàºòüñÿ êîìïåíñàòîðíà ã³ïåð³íñóë³íåì³ÿ, ÿêà ìîaeå ïðèçâîäèòè äî ðîçâèòêó ã³ïåðóðèêå쳿 òà ã³ïåð-òåí糿, çá³ëüøóþ÷è ðåàáñîðáö³þ ÑÊ ³ íàòð³þ â íèðêîâèõ êàíàëüöÿõ [25]. Íà ïî÷àòêîâèõ ñòàä³ÿõ ÖÄ 2-ãî òèïó ïîøèðåíèì ÿâèùåì º íèðêîâà ã³ïåðô³ëüòðàö³ÿ, ÿêà ñóïðîâîäaeóºòüñÿ ã³ïåðóðèêîçóð³ºþ.…”
unclassified
“…However, the relationship between increased NEFA levels, insulin resistance and abnormal glucose tolerance is complex. We have shown strong cross‐sectional associations between impaired suppression of NEFAs and diabetes[76], and features of MS[77]. Moreover we have recently undertaken a prospective study following 481 women and 345 men over 4.5 years and shown that there were only cross‐sectional and not longitudinal associations between increased NEFA levels and glucose intolerance and other features of MS[78].…”
Section: Pathophysiology Of Adipocyte Function Relevant To the Metabomentioning
confidence: 99%